2006
DOI: 10.1016/j.jbbm.2006.02.005
|View full text |Cite
|
Sign up to set email alerts
|

New model substrates for enzymes hydrolysing polyethyleneterephthalate and polyamide fibres

Abstract: Recently the potential of enzymes for surface hydrophilisation and/or functionalisation of polyethyleneterephthalate (PET) and polyamide (PA) has been discovered. However, there was no correlation between enzyme class/activity (e.g. esterase, lipase, cutinase) and surface hydrolysis of these polymers and consequently no simple assay to estimate this capability. Enzymes active on the model substrates bis (benzoyloxyethyl) terephthalate and adipic acid bishexyl-amide, were also capable of increasing the hydrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
134
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(144 citation statements)
references
References 21 publications
0
134
0
4
Order By: Relevance
“…All other chemicals were of analytical grade from SIGMA (Germany) except the model substrate bis(benzoyloxyethyl)terephthalate (3PET) which was synthesized in two steps as previously described [40].…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…All other chemicals were of analytical grade from SIGMA (Germany) except the model substrate bis(benzoyloxyethyl)terephthalate (3PET) which was synthesized in two steps as previously described [40].…”
Section: Chemicalsmentioning
confidence: 99%
“…Hydrolysis of the model substrate bis(benzoyloxyethyl)terephthalate (3PET) has been proven first to be valuable for the screening of enzymes capable of PET hydrolysis [40] and to provide important mechanistic information [27,32,34,42] about the type of hydrolysis mechanism. In the case of the new esterase Thh_Est, the hydrolysis product found in highest concentration was BA, followed by HEB, both in a comparable concentration higher than 50 mmol per mol of enzyme.…”
Section: Hydrolysis Of the Pet Model Substrate Bis(benzoyloxyethyl)tementioning
confidence: 99%
“…This can be cost-effective and ecofriendly method in textile industry. Some thermophilic Actinomycetes such as Pseudonocardia thermophila are known producers of nitrile hydratase which is used in the biotransformation of nitriles into different useful compounds, e.g., amides, amines, esters, aldehydes and ketones [38]. Alginate lyases hydrolyze different polysaccharides to produce alinate which has potential to be used as antitumor agent, anticoagulant and anti-inflammatory agent [39].…”
Section: Lipasesmentioning
confidence: 99%
“…(Negoro et al, (1980) pointed that Flavobacterium are able to degrade 6-aminohexanoic cyclic dimer (waste of nylon 6) at 30 °C. It was found that the optimum temperature for 6-aminohexanoate oligomer hydrolase enzyme was between 30°C and 45°C (Heumann et al, 2008). Anoxybacillus is a mild thermophile.…”
Section: Effect Of Phmentioning
confidence: 99%